The Legal Classification of Cryptocurrency in South African Law: An Argument for Classification as Currency. - Harvey, Nicola Ann (Department of Commercial Law, 2020)
Cryptocurrency - and indeed the underlying blockchain technology in general - have the potential to become a dominant method of effecting the transfer of value in a manner that fundamentally shifts the way in which electronic transactions take place. South Africa is a strong emerging market with the potential to attract substantial investment in new technologies should its regulatory response to such innovation remain principled. The primary purpose of this dissertation is to investigate the most appropriate classification of cryptocurrency in South African law. The research is qualitative in nature. It considers selected aspects of the existing legislative framework and scholarly opinion in determining whether cryptocurrency is best classified as property or as currency. The necessary corollary of this research focus is to consider the fundamental importance of such a classification for legal policy design generally, and the practical effects thereof. This dissertation hypothesises that the value of the blockchain technology lies in its commercial viability and its potential scalability, particularly in the African context. Thus, the required objective of regulatory intervention should be to preserve the commercial viability of cryptocurrency and avoid stifling technological advancement, whilst simultaneously ensuring the protection of vulnerable users. The conclusion is that cryptocurrency is best classified as foreign currency. This dissertation acknowledges that although it is possible to fit such a classification into existing legislative frameworks, a more specialised structure is ultimately required. Additionally, it raises concern about the harm caused by reactive regulatory intervention and instead recommends a principled policy approach, cognisant of the need for maturation of the technology.